2012
DOI: 10.1002/jsfa.5844
|View full text |Cite
|
Sign up to set email alerts
|

Development of a freeze‐dried mixture of Nile tilapia (Oreochromis niloticus) croquette using a GA‐based multiobjective optimisation

Abstract: The GA-based approach was able to optimise the croquette formulation. The freeze-drying process contributed to the development of a value-added product with high quality and long shelf-life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 36 publications
1
15
1
Order By: Relevance
“…similar to this experiment were obtained in lyophilized mixtures of fish croquettes at time zero with the same main ingredient as the MSM of the Nile tilapia (Fuchs et al, 2013) and in croquettes of the MSM of tilapia after being pre-fried, (Bordignon et al, 2010) for Salmonella sp., Coliforms at 45°C, B. cereus and S. coagulase. However, higher values were found in 4 types of prepared fishburger with the MSM of the Nile tilapia for E. coli and coliforms at 45°C (Marengoni et al, 2009) and lower values for viable mesophilic and psycotrophic aerobic bacteria (Bordignon et al, 2010).…”
supporting
confidence: 73%
“…similar to this experiment were obtained in lyophilized mixtures of fish croquettes at time zero with the same main ingredient as the MSM of the Nile tilapia (Fuchs et al, 2013) and in croquettes of the MSM of tilapia after being pre-fried, (Bordignon et al, 2010) for Salmonella sp., Coliforms at 45°C, B. cereus and S. coagulase. However, higher values were found in 4 types of prepared fishburger with the MSM of the Nile tilapia for E. coli and coliforms at 45°C (Marengoni et al, 2009) and lower values for viable mesophilic and psycotrophic aerobic bacteria (Bordignon et al, 2010).…”
supporting
confidence: 73%
“…The higher content of these saturated fatty acids and the lower proportion of mono and polyunsaturated fatty acids may increase the incidence of coronary disease. In this study, the values of IA and IT (Table 4) were higher than were the ones reported by Souza et al (2015), Silva et al (2014b), andFuchs et al (2013a), who used flaxseed flour in the products.…”
Section: Resultscontrasting
confidence: 76%
“…The portion destined for the lyophilization method was separated in portions of approximately 150 g, before then being arranged in 17 cm in diameter trays and dried using the Liotop lyophilizer (L101 model). The conditions for the pre-freezing and lyophilization drying processes were performed according to those proposed by Fuchs et al (2013a). After the conventional and lyophilization drying processes, the samples were ground in a hammer mill to obtain a flour with a particle size of 14-16 mesh.…”
Section: Preparation Of Flourmentioning
confidence: 99%
See 1 more Smart Citation
“…In the acceptability test a hedonic scale of nine points (9 being ‘like extremely’ and 1 ‘dislike extremely’) was used . Fifty‐six tasters took part in these tests; this number was justified by the large number of formulations to be tested and was in accordance with other published works . The samples were served in plastic cups, coded with three random digits, containing a small piece of cake of approximately 2 g. The samples were presented to the tasters randomly, in a monadic fashion, along with an individual evaluation form.…”
Section: Methodsmentioning
confidence: 99%